Histone demethylase KDM1A represses inflammatory gene expression in preadipocytes. (5th July 2013) - Hanzu, Felicia A.; Musri, Melina M.; Sánchez‐Herrero, Alvaro; Claret, Marc; Esteban, Yaiza; Kaliman, Perla; Gomis, Ramon; Párrizas, Marcelina
<x xml:space="preserve">Abstract</x> Objective Persistent inflammation and impaired adipogenesis are frequent features of obesity and underlie the development of its complications. However, the factors behind adipose tissue dysfunction are not completely understood. Previously it was shown that histone demethylase KDM1A is required for adipogenesis. Design and Methods Kdm1a expression was knocked down in 3T3‐L1 preadipocytes by siRNA transfection and whole‐genome expression profiling was performed by microarray hybridization. The role of NF‐κβ and C/EBPβ was analyzed by incubation with the inhibitor parthenolide and by cebpb knockdown, respectively. Results Knockdown of kdm1a or rcor2 in 3T3‐L1 preadipocytes results in impaired differentiation and induction of inflammatory gene expression. Enhanced expression of il6 in kdm1a knocked down preadipocytes is associated with increased recruitment of C/EBPβ and the NF‐κβ subunit RelA to the il6 promoter. Cebpb knockdown attenuates the induction of il6 expression in kdm1a knocked down cells, whereas simultaneous cebpb knockdown and NF‐κβ inhibition abrogates it. Dietary‐induced and genetic mouse models of obesity display decreased KDM1A in adipose tissue, and this correlates with increased expression of proinflammatory genes and C/EBPβ. Conclusion KDM1A represses the expression of inflammatory genes in preadipocytes. Dysregulated kdm1a expression in preadipocytes may thus participate in the development of obesity‐associated inflammation.